Efektivitas Peer Counseling Berbasis Health Belief Model Terhadap Pengetahuan Gizi Remaja di SMA Kota Binjai - Crystandy, Muhammad; Yulita, Yulita (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Adolescence is a critical period for the formation of long-term eating patterns, yet it is vulnerable to nutritional problems. The lack of effective nutrition education in schools is a major contributing factor. Innovative interventions are needed to improve healthy nutritional behavior. This study aims to determine the effectiveness of Peer Counseling education based on the Health Belief Model (HBM) in improving nutritional knowledge in adolescents. This study used a quasi-experimental design with a pre-test and post-test approach without a control group, conducted in five high schools in Binjai City. The study sample consisted of 213 students selected using a cluster sampling technique. The intervention was delivered by 10 students who had been trained as peer counselors using a module developed based on the Health Belief Model framework. Data analysis was performed using the Wilcoxon Signed-Rank Test. The results showed a highly significant increase in adolescents’ nutritional knowledge after the intervention. The average knowledge score more than doubled, from 12.04 at the pre-test to 26.49 at the post-test. The statistical test results showed a significance value of p=0.000 (p<0.05), indicating that the HBM-based Peer Counseling intervention was statistically effective. In conclusion, the Peer Counseling educational model integrated with the Health Belief Model framework proved effective in significantly improving nutritional knowledge among high school students. This approach successfully leveraged the influence of peers as agents of positive change. It is recommended that schools and health offices adopt this model as part of health promotion programs, such as school health programs, for sustainable adolescent nutritional empowerment.